Materials for astronautic vehicles - Murphy, A. J. (College of Aeronautics, 1960)
The nature of the environment in outer space and its significance for materials of construction of astronautic vehicles are considered. The most advanced experience with heat-resisting engineering materials has been gained in gas turbine applications. The potential developments towards higher operating temperatures of alloys based on iron, nickel and cobalt are approaching exhaustion. The next stage may use the higher melting point metals, especially molybdenum, columbium and tungsten, non-metallics such as carbon and ceramics, or combinations of metals and ceramics. The s refractory metals are capable of stressed service at 2500[degrees]F. (1370[degrees]C.) and higher, if means of protection against oxidation can be found. On the same condition graphite can be used for much higher temperatures. For the ballistic missile, ablation of surface layers on the nose cone offers the best prospect of successful heat-dissipation. The ablating material may be an organic material, e.g. synthetic resin, or a ceramic compound. For longer spells at high temperatures, as in satellites on re-entry, the alternatives are thermal insulation by nonmetallic surface coatings, and skins of metals having very high melting points. Coatings which provide insulation and protection from oxidation are provided as flame-sprayed ceramic oxides, especially alumina and zirconia, or ceramics reinforced by a refractory metal grid attached to the base metal. The major technical difficulties in applying the refractory metals to service at very high temperatures arise from their reactivity with ambient gases, especially oxygen, and their tendency to brittleness at low and moderate temperatures. Characteristics of materials which acquire special importance in astronautic applications are: thermal conductivity, specific heat, latent heat of fusion and evaporation, coefficient of thermal expansion, reactivity at high temperatures, sensitivity to irradiation, creep strength and resistance to high fatigue stresses at high temperatures and mechanical properties at low temperatures.